1979
DOI: 10.1159/000153021
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Indian Childhood Cirrhosis

Abstract: Detailed pedigree charts were prepared from 120 index patients suffering from Indian childhood cirrhosis (ICC). Of the 120 families, 84 were informative for segregation analysis. Since families were ascertained through patients who came to hospital for treatment, the data were analyzed according to a single-selection model. The observed segregation ratio for the entire data was significantly lower than the one expected under the hypothesis of autosomal recessive inheritance (p = < 0.005). On the other hand, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…Moreover, the families of different sizes exhibited the same pattern of segregation. Agarwal et al [1979] have also reported a similar finding. DAR hy pothesis of inheritance was also found to be untenable.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, the families of different sizes exhibited the same pattern of segregation. Agarwal et al [1979] have also reported a similar finding. DAR hy pothesis of inheritance was also found to be untenable.…”
Section: Discussionsupporting
confidence: 63%
“…(I-0"> 0"(Xts-X ns) Since the age of onset of ICC is variable it is necessary to adjust the expected segregation ratio by multiplying it with the mean age-dependent pe-netrancc parameter K which was taken as 0.87 as reported by Agarwal et al [ 1979], Partially Sex-Linked Recessive (PSLR) Inherit ance Hypothesis. Since from the data it was not possible to know the phase of linkage of the hetero zygous male parent, the most generally efficient method for testing the hypothesis is that of Fisher's u statistic [Fisher, 1935.…”
Section: Monofactorial Hypothesismentioning
confidence: 99%
“…The fatal, early onset disorder Indian childhood cirrhosis, which may have both genetic and environmental contributions (35,36), is similar to Wilson disease in that copper accumulates in the liver and seems unlikely to be due to mutations in a ubiquitously expressed gene. Thus the involvement of hCTR1 or hCTR2 with an inherited human condition remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…< 121.3~). This estimate suggests a genetic influence of between 88 and 100K, and is equivalent to those of the radial border termination of the thenar crease on the palm (Tay, 1979) and Indian childhood cirrhosis (Agarwal et al, 1979). Accordingly, analysis by the Falconer method suggests a possibility that the missing c triradius is of multifactorial origin with very strong genetic determination (over 88~).…”
Section: Resultsmentioning
confidence: 92%